Impact of climate change on wood and woodworkers—Cryptostroma corticale (sooty bark disease): A risk factor for trees and exposed employees - Kespohl, Sabine; Riebesehl, Janett; Grüner, Jörg; Raulf, Monika (Frontiers in Public Health, 2022)
Climate changes have promoted an increased fungal infection of maple trees with Cryptostroma corticale, the causative agent of sooty bark disease. The hosts of C. corticale are maples, and since the early 2000s the fungus has been appearing more frequently in European forests, due to the droughts and hot summers of recent years. Infestation by C. corticale discolours the wood and makes it unusable for further processing, which leads to considerable economic damage in the timber industry. Therefore, the occurrence and spread of sooty bark disease raise serious problems. In addition to forestry and economic problems, the conidiospores of C. corticale can also cause health problems in exposed wood workers and they can trigger hypersensitivity pneumonitis (HP). Since the spores, which are deposited over the entire area under the bark of infected trees, can spread during processing, exposed workers must take special precautions to protect themselves against exposure. If an occupational disease is nevertheless suspected following exposure to C. corticale, valid diagnostics are required to confirm possible HP and derive appropriate therapies and exposure reduction or avoidance. Diagnosis of HP is based on several criteria, one of them is the detection of specific IgG in patient’s serum against the potentially triggering antigens, in this case C. corticale antigens. To produce a diagnostic tool to measure C. corticale specific IgG, which is not commercially available so far, spores and mycelial material from ITS-sequenced strains of C. corticale was prepared and analysed. These biochemically characterized extracts of spore and mycelial antigens were biotinylated and coupled to Streptavidin-ImmunoCAPs. To validate these diagnostic test tools the first step is to measure the concentration of C. corticale specific IgG in sera of healthy non-exposed and healthy exposed subjects to establish cut-off values. Suitable participants were recruited and the individual exposure to C. corticale and symptoms experienced during or after working with infected maple trees were recorded using questionnaires. Finally, diagnostic tools for serological testing in suspected cases of HP by C. corticale were created and evaluated.